GROWING OF PEA PLANT AND FIGHTING ITS DISEASES IN THE CONDITIONS OF KASHKADARYA REGION - Mamajonova Gulziyoda Erkinjon qizi (Journals Park Publishing, 2024)
Pea is considered one of the most important crops in world agriculture among leguminous crops and is planted annually on an area of millions of hectares. Of this, the area planted with legumes is 20-25%. In terms of cultivated area, soybeans, chickpeas, green peas and lentils are being planted in the main large areas.
Keywords: Legume, fusarium, askachitosis, powdery mildew, nematode, releft, fungus, petri, pea, grain, hay, mycelium, food, thermostat.